Conditional Release Policy to Resolve Overcapacity in Correctional Institution - Dean Anugra, Muhammad; Susanti, Emilia (Veteran Law Review, 2024)
As a place to rehabilitate convicts, correctional institutions foster convicts to become better person with a good character, independence, skill, discipline and awareness of the law. This is in accordance with the function of the correctional system which is a system of treatment of convicts, which follows the renewal of prison sentences based on Pancasila and the principles of humanity. The problem is, currently the majority of correctional institutions in Indonesia have over capacity problems. This over capacity has the potential to become various problems. An example is the monitoring and rehabilitation of convicts that doesn't work properly, and even spends a lot of budget on operational costs. The problem of overcapacity which certainly has an impact on various aspects of life in prisons or detention centers which tends to be dysfunctional towards the achievement of correctional goals. The conditional release policy for convicts who prioritizes the principles of rehabilitating can be used as a solution in solving various problems and accommodating legal needs in society. The establishment of this arrangement is also part of an effort to harmonize regulations in order to create a correctional system that is oriented towards protecting human rights in the 1945 Constitution of the Republic of Indonesia.